COMPARATIVE EVALUATION OF ORAL MELATONIN AND ORAL PREGABALIN AS PREMEDICATION FOR PREOPERATIVE ANXIETY AND ATTENUATION OF HEMODYNAMIC RESPONSE TO LARYNGOSCOPY AND TRACHEAL INTUBATION: A PROSPECTIVE RANDOMISED STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Preoperative anxiety is a common concern among surgical patients and is associated with adverse perioperative outcomes, including exaggerated hemodynamic responses during laryngoscopy and tracheal intubation. Pharmacological premedication plays a key role in alleviating anxiety and maintaining hemodynamic stability. Melatonin, a neurohormone with anxiolytic and sedative properties, and pregabalin, a GABA analogue with anxiolytic and analgesic effects, have been increasingly studied for this purpose. This study aimed to compare the efficacy of oral melatonin and oral pregabalin in reducing preoperative anxiety and attenuating hemodynamic responses to laryngoscopy and intubation. Material and Methods: This prospective, randomized, double-blind controlled study included 60 patients (ASA I–III) aged 30–60 years undergoing elective surgery. Patients were randomly allocated into two groups of 30 each: Group M received oral melatonin 6 mg, and Group P received oral pregabalin 75 mg, one hour before induction. Preoperative anxiety was assessed using the APAIS scale. Hemodynamic parameters (HR, SBP, DBP, MAP) were recorded at baseline, during intubation, and at 1, 5, and 10 minutes post-intubation. Data were analyzed using appropriate statistical tests with p